Perspectivas de la investigación lingüística en Hispanoamérica. Ed. J. M. Lope Blanch. UNAM, México, 1980; 140 pp. - Madrigal, Mariana P. (El Colegio de México, 1982)
Se reseñó el libro: Perspectivas de la investigación lingüística en Hispanoamérica. Ed. J. M. Lope Blanch.